2022
DOI: 10.3390/jcm11226799
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Soluble Angiotensin Converting Enzyme 2 (sACE2) in Children and Adults with and without COVID-19

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), causing the coronavirus disease 2019 (COVID-19) pandemic, leads to illness and death. Various risk factors for a severe course, such as higher age, male gender and pre-existing illnesses are known. However, pathophysiological risk factors are largely unclear. Notably, the mild course of disease in children is conspicuous. Angiotensin converting enzyme 2 (ACE2) serves as a receptor for SARS-CoV-2 and is a key enzyme in infection. Differences in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Therefore, studies mostly investigate the blood levels of these enzymes and their relationships with the occurrence and prognosis of COVID-19. 10,14,15 These studies are mostly related to the adult population and examine ACE2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, studies mostly investigate the blood levels of these enzymes and their relationships with the occurrence and prognosis of COVID-19. 10,14,15 These studies are mostly related to the adult population and examine ACE2.…”
Section: Discussionmentioning
confidence: 99%
“…20 Some studies have shown positive prognostic results with the use of human recombinant sACE2 in COVID-19. 10,21 However, previous studies suggest that high blood ACE2 concentration is associated with COVID-19 severity 10,22 and also some comorbidities 22,23 that influence the prognosis of COVID-19. 5, 24 Ciaglia et al 7 speculated that the reason for these paradoxes may lie in posttranslational events that regulate protein levels and their balance between membrane-bound and soluble forms of ACE2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-lasting, passive protection was achieved suggesting such an approach could be used to treat COVID-19 patients. On the other hand, high plasma level of sACE2s is often observed in COVID-19 patients with severe illness and increases with age ( Akin et al, 2022 ; Wissing et al, 2022 ), raising questions on whether sACE2 therapy will be beneficial to these patients.…”
Section: Sars-cov-2 Entry Inhibitors In Clinical and Preclinical Testingmentioning
confidence: 99%
“…It has also been reported that sACE2 has also been used as a prognostic marker for the severity of the disease. Higher the level of sACE2, more severe is the disease 26,27 …”
Section: Introductionmentioning
confidence: 99%